Efektifitas Pembelajaran Daring Di Era Pandemi Covid-19 Pada SMK Mandalla Entrepreneur School Karawang - irfan mujahidin; Syamsudin Kastoer (Thawalib: Jurnal Kependidikan Islam, 2021)
The aim of this research is to know how much effectiveness of online learning during the pandemic 19 for the students of SMK Mandalla Entrepreneur School Karawang District. The study used quantitative models with survey methods. The sample of respondents of this study are the students of every level randomly amounted to 73 students. The results of this study showed that 8 students or about 10.96% of respondens have not felt the benefits of online learning. Students' responses to online learning are also less enthusiastic, as seen from the data of about 37 students or 50.68% of students feeling bored. Then the desire of students, learning is carried out face-to-face directly with data showed about 65 students from 73 respondents or about 89.04%, about 5 students or 6.85% learning in a block system, namely one day of online learning and one day face-to-face learning, and 3 students or 4.11% who want online learning so it could be concluded that continuous online learning during the pandemicera is very ineffective.